Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T17:02:03+01:00
A). 2(3x+2)-3(5x-6)+4(7x+8)=111
6x + 4 -15x + 18 + 28x +32 = 111
19x = 57 | :19
x = 3

b).x+15=8 1/3
x = 8 1/3 - 15
x = - 6 2/3

c).-3x=3 3/4 | : (-3)
x = (15/4) : (-3)
x = -15/12
x = -1 2/12

d).x/7=4/5 |*7
x = 28/5
x = 5,6
2010-02-23T17:07:18+01:00
Zad1.
a). 2(3x+2)-3(5x-6)+4(7x+8)=111
6x+4-15x+18+28x+32=111
6x-15x+28x+18+32+4=111
6x+13x+50+4=111
19x+50=107
19x=57/:19
x=3
b).x+15=8 1/3
x=8 1/3-15
x=-6 2/3
c).-3x=3 3/4
-3x=15/4 /:(-3)
x=-15/12
x=-5/4=-1,25
d).x/7=4/5 /^7
x=28/5=5 3/5=5,6